Religion on Which the Devout and Skeptic Can Agree - Rossano, Matt J. (Zygon, 2007)
Abstract. A starting point for a constructive exchange between two groups, devout religionists and scientific skeptics, is that they can hold certain religious ideas in common. These ideas, however, must preserve the compelling nature of religious commitment without unduly compromising rational sensibilities. In the histories of both science and religion progress has been made by synthesis. The definition of religion is a key issue for the success or failure of synthesis, and I propose a new definition. Both devout religionists and scientific skeptics must make compromises if synthesis is to be successful. For the devout these compromises include waiving the prerequisite of belief in the supernatural and placing behavior above belief. For the skeptic they include abandoning explanatory exclusivity, acknowledging the authority of moral experts, and recognizing the necessity of community in achieving moral excellence. I defend each of these compromises as reasonable and tolerable costs of integration.